PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN PEMAHAMAN MATERI GAYA DAN GERAK - Anis Khoerunisa; Rita Istiana; Yudhie Suchyadi (STKIP Subang, 2023)
This study is a research and development model of the ADDIE (Analysis, Design, Development, Implementation, Evaluation) conducted from November to October 2022. This study aims to develop student worksheets (LKPD) based on problem based learning (PBL) to improve understanding of the fourth grade students of SDN Sukasirna 01 with the material of force and motion. The research target is class IV SDN Sukasirna 01 for the experimental class, which consists of 20 students and uses one group pretest-posttest. The instruments used in this study consisted of expert validation sheets, student understanding test questions, and teacher and questionnaire responses of teacher and students to LKPD based on PBL. The results show that 1) LKPD based on PBL can improve students' understanding as indicated by an average N-Gain of 0.61 (medium), 2) the results of expert validation of the quality of PBL-based LKPD can be categorized as very feasible and meet the criteria, 3) teacher responses and students to PBL-based LKPD gave a positive response. 4) Suggestions and recommendations from this research, it is hoped that further researchers will develop PBL-based E-LKPD and be tested widely.